2019
DOI: 10.1038/s41746-019-0189-7
|View full text |Cite|
|
Sign up to set email alerts
|

Human–machine partnership with artificial intelligence for chest radiograph diagnosis

Abstract: Human-in-the-loop (HITL) AI may enable an ideal symbiosis of human experts and AI models, harnessing the advantages of both while at the same time overcoming their respective limitations. The purpose of this study was to investigate a novel collective intelligence technology designed to amplify the diagnostic accuracy of networked human groups by forming real-time systems modeled on biological swarms. Using small groups of radiologists, the swarm-based technology was applied to the diagnosis of pneumonia on ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 143 publications
(120 citation statements)
references
References 45 publications
3
110
1
6
Order By: Relevance
“…This indicates that AKIRA complemented human labelling and thereby enhanced its own accuracy. Such 'human in the loop' iteration methods are effective for AI systems that generate training data based on human judgement, as previously reported by another group 24 .…”
Section: Discussionsupporting
confidence: 64%
“…This indicates that AKIRA complemented human labelling and thereby enhanced its own accuracy. Such 'human in the loop' iteration methods are effective for AI systems that generate training data based on human judgement, as previously reported by another group 24 .…”
Section: Discussionsupporting
confidence: 64%
“…29 Furthermore, human-machine partnerships can provide far better results than either humans or machines alone. 30 In these examples, the principal benefits of artificial intelligence stem from its ability to improve efficiency and effectiveness by guiding diagnoses, delivering more accurate results and thus eliminating human error. With regard to greater efficiency through prevention, artificial intelligence technologies that track and analyse the movement of individuals could be used to detect people at risk of stroke and eliminate that risk through early intervention.…”
Section: Artificial Intelligence In Health Carementioning
confidence: 99%
“…We would like to emphasize that we propose this model as a clinical decision support system to improve physician accuracy and efficiency in the clinical workflow, not as a replacement or a tool that can directly output a diagnosis. It has been shown that human–machine combination works better than either alone 39 41 . While it is possible to make a machine learning model that can directly output a diagnosis, we consider such black box approaches to be unsuitable for high stakes decisions like medical diagnosis.…”
Section: Discussionmentioning
confidence: 99%